Technology and Training Needs Assessment of Farm Women in Andhra Pradesh - B. Renuka Rani; B. Venkata Rao (Journal of Agricultural Extension Management, 2014)
Women play a significant and crucial role in agricultural production and development processes. They perform a variety of agricultural operations physically, mostly drudgery filled and manage the livestock production activities. Kitchen gardening and poultry keeping are also the exclusive jobs of women, besides home making. The role of farm women in agricultural development is substantial and their involvement in transfer of technologies is becoming more and more crucial due to the changing socio-economic environment. Therefore, it is imperative to understand the Technology and Training Needs of farm women in the transfer of farm technologies from the laboratories to the land.